REBACIN® inhibits E6/E7 oncogenes in clearance of human papillomavirus infection - Zhou, Shu-Guang; Wu, Dai-Fei; Yao, Hui; Zhang, Wei-Yu; Tian, Feng-Jiao; Chen, Guo; Zhang, Chun-Fa (Frontiers in Oncology, 2022)
Previous studies have demonstrated that REBACIN® intervention eliminates persistent high-risk human papillomavirus (hrHPV) infection. The initial establishment and subsequent progression of cervical cancer mainly depends on two major oncogenes, E6/E7, and previous studies have proposed E6/E7 oncogenes as a target for therapeutic drug development. The aim of this study was to investigate in vitro and in vivo whether REBACIN® inhibits E6/E7 oncogenes for elucidating the mechanism of REBACIN® in the clearance of persistent hrHPV infection. In vitro, after REBACIN® treatment, the growth of both Ca Ski and HeLa cervical cancer cells containing the E6/E7 oncogenes was prevented. In line with this finding is that E6/E7 expression was inhibited, which can be counteracted by the co-application of anti-REBACIN® antibody. These studies demonstrated that REBACIN® can effectively inhibit the growth of cervical cancer cells via targeting HPV E6/E7 expression. To further verify this finding in clinic, 108 volunteer patients with persistent hrHPV infections were randomly divided into REBACIN®, recombinant human interferon alpha-2b (Immunological drug control), or no-treatment blank control groups, received intravaginal administration of REBACIN®, interferon or no-treatment every other day for three months, and then followed up for E6/E7 mRNA assay. In REBACIN® group, 68.57% of patients showed complete clearance of HPV E6/E7 mRNA, which was significantly higher compared to 25.00% in the interferon immunological drug control group and 20.00% in blank control group, confirming that REBACIN® is potently efficacious on clearing persistent hrHPV infections via inhibition of HPV E6/E7 oncogenes. Clinical trial registration http://www.chictr.org.cn/historyversionpuben.aspx?regno=ChiCTR2100045911, identifier ChiCTR2100045911.